Method for preparing gamma-Fe2O3-clay loaded hydrotalcite-like compound phosphorus removal agent by using natural iron-containing clay
By using the acid-implanted waste liquid of natural iron-containing clay, the problems of resource waste and environmental pollution are solved, and the efficient utilization of natural iron-containing clay and the effective removal of phosphate in water are achieved.
Patent Information
- Application Number
- CN202411832050.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to effectively utilize the acid-leaching waste liquid of natural iron-containing clay, resulting in waste of resources and environmental pollution.
Using an integrated modification strategy, γ-Fe2O3 is prepared as a magnetic core by Fe3+ in the acid-implanted waste liquid of natural iron-containing clay, and combined with acid-activated clay to form a magnetic carrier of γ-Fe2O3@clay, and a γ-Fe2O3@clay-loaded hydrotalcite phosphorus removal agent is prepared by adding ZrOCl2 secondary acid-implanted waste liquid as a metal ion source.
Comprehensive modification and utilization of natural iron-containing clay has been achieved. The prepared phosphorus removal agent can effectively adsorb low-concentration phosphate in water and is easy to be magnetically separated and recovered.
Smart Images

Figure CN119608102A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmentally friendly adsorption materials, relates to a hydrotalcite dephosphorizing agent, and specifically relates to a method for preparing a γ-Fe2O3@clay-loaded hydrotalcite dephosphorizing agent by utilizing natural iron-containing clay. Background Art
[0002] The attapulgite clay from Hangjin, Ordos, Inner Mongolia Autonomous Region is a mixed-dimensional clay mineral, mainly containing attapulgite, illite, chlorite, calcite and quartz, etc. It is rich in a large amount of amorphous iron oxide, reddish brown in color, and has a high specific surface area. Acid treatment is a common step in modifying clay for the preparation of functional materials such as adsorbents, decolorizers, and molecular sieves. It produces a large amount of acid leaching waste liquid containing metal ions, which pollutes the environment and is also a waste of resources, which is not conducive to the high value-added development and utilization of clay resources. How to effectively utilize acid leaching waste liquid is an issue that must be paid attention to in the green, sustainable and high value-added application of clay resources. The reported methods for preparing magnetic adsorbents using natural clay usually prepare magnetic iron oxide by adding an external iron source. For example, Liu Tingting et al. prepared magnetic (Fe3O4) nano-iron / montmorillonite clay using FeSO4 and FeCl3 as iron sources, and used it to adsorb Pb 2+ (Journal of the Chinese Ceramic Society, 2017, 45(01): 29-36); Chinese patent (ZL.202011205622.X) discloses a method for preparing a magnetic mesoporous composite adsorbent using natural mixed clay, and its magnetic source is also Fe3O4 prepared by adding divalent and trivalent iron salts.
[0003] The purpose of the present invention is to propose an integrated modification strategy, using the iron ions in the acid leaching waste liquid of natural iron-containing clay to prepare magnetic γ-Fe2O3, using it as the core, and constructing a γ-Fe2O3@clay magnetic carrier with acid-activated clay, and finally using the secondary acid leaching waste liquid with a small amount of ZrOCl2 added as the metal ion source to prepare a γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorizer, which can effectively adsorb low-concentration phosphate in water and is easy to be separated and recovered by magnetic separation. Summary of the invention
[0004] In order to solve the problem of resource utilization of clay acid leaching waste liquid, the present invention provides a method for preparing a γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorizing agent by using natural iron-containing clay.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing a γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorizing agent using natural iron-containing clay, comprising acid modification of the natural iron-containing clay, wherein the natural iron-containing clay is dissolved during the acid modification process to produce a hydrotalcite containing various metal ions (mainly Mg 2+ , Ca 2 + 、Al3+ , Fe 3+ ) acid leaching wastewater, using Fe 3+ γ-Fe2O3 was prepared as the magnetic core and composited with acid-activated clay to form a core-shell type γ-Fe2O3@clay magnetic carrier. Then, the secondary acid leaching waste liquid with a small amount of ZrOCl2 added was used as the metal ion source to prepare the γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorus agent.
[0007] The above method of the present invention specifically comprises the following steps:
[0008] Step 1: After washing, filtering, drying and grinding, the natural iron-containing clay is mixed with 100 mL of a 3 mol / L hydrochloric acid aqueous solution, stirred and refluxed at 80° C. for 4 h, and solid-liquid separation is performed after cooling to obtain acid leaching waste liquid and activated clay, the latter of which is washed with water and dried for later use;
[0009] Wherein, the natural iron-containing clay is Inner Mongolia Hangjin attapulgite clay;
[0010] Step 2: Add 2 mol / L NaOH solution to the acid leaching waste liquid obtained in step 1 until the pH is 5.2, centrifuge to obtain secondary acid leaching waste liquid and iron hydroxide wet precipitate, mix the latter with glacial acetic acid and stir for 1 hour, hydrothermally crystallize at 100°C, filter after natural cooling, dry at 80°C for 24 hours, and calcine at 400°C under Ar atmosphere for 2 hours to obtain magnetic γ-Fe2O3;
[0011] The molar ratio of the wet precipitate of iron hydroxide to glacial acetic acid is 1:6 to 12, preferably 1:6, and the hydrothermal crystallization time is 12 to 48 hours, preferably 24 hours;
[0012] Step 3: The activated clay obtained in step 1 and the γ-Fe2O3 obtained in step 2 are dispersed in an ethanol aqueous solution with an ethanol / water volume ratio of 4:1 according to a certain mass ratio, stirred evenly, separated into solid and liquid, and the solid was vacuum dried at 60° C. for 12 h to obtain a magnetic γ-Fe2O3@clay carrier;
[0013] Wherein, the mass ratio of the activated clay to γ-Fe2O3 is 10-30:1, preferably 20:1, and the stirring time is 4-10 hours, preferably 6 hours.
[0014] Step 4: Add 1.0 g of the γ-Fe2O3@ clay obtained in step 3 to 20 mL of 0.0001 mol / L NaOH solution, stir at room temperature to obtain a turbid solution S1, add ZrOCl2 to the secondary acid leaching waste liquid obtained in step 2 to obtain a salt solution S2, and add 5 to 20 mL of S2 dropwise to S1 under room temperature stirring, and simultaneously add 1 mol / L NaOH solution to control the pH of the mixed solution to 9.5 to 10.5. After the addition of S2 is completed, the mixed solution is hydrothermally crystallized at 110° C. for 12 h, cooled naturally, and centrifuged to separate the solid and liquid, and the solid is washed with water and dried at 80° C. overnight to obtain a γ-Fe2O3@ clay-loaded hydrotalcite-like dephosphorizer;
[0015] Among them, the addition amount of ZrOCl2 in the secondary acid leaching waste liquid is 0.011-0.088g, preferably 0.022g, and S2 is preferably 10mL.
[0016] The γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorizing agent prepared by the method of the present invention is used in the adsorption of low-concentration phosphate in water.
[0017] The test method for the adsorption of low-concentration phosphate by γ-Fe2O3@clay-loaded hydrotalcite dephosphorization agent is as follows: 100 mg of the γ-Fe2O3@clay-loaded hydrotalcite dephosphorization agent is added to 25 mL of simulated phosphate wastewater (pH = 2) with a phosphate content of 10 mg / L, and after oscillation at room temperature for 2 hours, magnetic solid-liquid separation is performed using a neodymium iron boron permanent magnet, and the clarified solution is subjected to continuous flow-ammonium molybdate spectrophotometry (determination of phosphate and total phosphorus in water quality, HJ 670-2013), and data is collected using a spectrophotometer at a wavelength of 880 nm to calculate the removal rate.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention adopts an integrated modification strategy, using natural iron-containing clay as raw material and utilizing the Fe 3+ γ-Fe2O3 is prepared as a magnetic core, and a core-shell type γ-Fe2O3@clay magnetic carrier is composited with acid-activated clay. Then, the secondary acid leaching waste liquid with a small amount of ZrOCl2 added is used as a metal ion source to prepare a γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorizing agent, thereby realizing the comprehensive modification and utilization of natural iron-containing clay. The dephosphorizing agent developed by the present invention can effectively adsorb low-concentration phosphate in water and is easy to be magnetically separated and recovered.
[0020] 2. The preparation method of the present invention has a simple process, and the natural iron-containing clay used is not limited to the Inner Mongolia Hangjin attapulgite clay. By adjusting the specific process conditions, it can also be used to treat other natural iron-containing clays in my country, which is helpful to realize the high added value comprehensive development and utilization of natural iron-containing clay and improve its economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a process flow chart for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorizing agent;
[0022] Figure 2 This is the magnetic intensity curve of γ-Fe2O3@clay loaded hydrotalcite-like dephosphorization agent and the magnetic separation picture after use. DETAILED DESCRIPTION
[0023] The present invention is described in detail below in conjunction with specific embodiments and the accompanying drawings; it should be understood that the following embodiments are only intended to illustrate the technical solutions of the present invention and are not intended to limit the scope of the present invention in any way. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.
[0024] Unless otherwise specified, the instruments and reagents described in this example can be obtained from commercial sources.
[0025] In this embodiment, the removal rate (%) of phosphate = 100×(concentration of phosphate solution before reaction - concentration of phosphate solution after reaction) / concentration of phosphate solution before reaction.
[0026] The preferred preparation process of γ-Fe2O3@clay magnetic carrier is as follows:
[0027] After washing, filtering, drying and grinding the Hangjin attapulgite clay, it was mixed with 100 mL of 3 mol / L hydrochloric acid aqueous solution, stirred and refluxed at 80°C for 4 hours, and cooled to obtain acid leaching waste liquid and activated clay by solid-liquid separation. The latter was washed with water and dried for use. 2 mol / L NaOH solution was added to the obtained acid leaching waste liquid until pH = 5.2, and centrifuged to obtain secondary acid leaching waste liquid and iron hydroxide wet precipitate. The latter was mixed and stirred with glacial acetic acid at a molar ratio of 1:6 for 1 hour, hydrothermally crystallized at 100°C for 24 hours, naturally cooled and filtered, dried at 80°C for 24 hours, and calcined at 400°C under Ar atmosphere for 2 hours to obtain magnetic γ-Fe2O3. The secondary acid leaching waste liquid was retained for use.
[0028] The activated clay and the above-obtained γ-Fe2O3 were dispersed in an ethanol-water solution (ethanol / water volume ratio of 4:1) at a mass ratio of 20:1, stirred evenly for 6 h, centrifuged and dried in vacuo at 60 °C for 12 h to obtain a magnetic γ-Fe2O3@clay carrier, labeled as γ-Fe2O3@Clay.
[0029] The γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent was prepared using the above-mentioned preferred γ-Fe2O3@clay as a carrier as follows:
[0030] Example 1
[0031] 1.0 g of the preferred γ-Fe2O3@clay was added to 20 mL of 0.0001 mol / L NaOH solution and stirred at room temperature for 30 min to obtain a turbid solution S1. Under stirring at room temperature, 10 mL of the secondary acid leaching waste liquid was added dropwise to S1, and 1 mol / L NaOH solution was added dropwise to control the pH of the mixed solution to 9.5-10.5. After the secondary acid leaching waste liquid was added dropwise, the mixed solution was hydrothermally crystallized at 110°C for 12 h. After natural cooling, the solid-liquid separation was performed by centrifugation. The solid was washed with water and dried at 80°C overnight to obtain a γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorus agent (labeled as Zr0LDH / γ-Fe2O3@Clay).
[0032] The removal rate of Zr0LDH / γ-Fe2O3@Clay for 10 mg / L phosphate is 87.00%.
[0033] Example 2
[0034] 1.0 g of the preferred γ-Fe2O3@ clay was added to 20 mL of 0.0001 mol / L NaOH solution and stirred at room temperature for 30 min to obtain a turbid solution S1. 0.011 g of ZrOCl2 was added to 10 mL of the secondary acid leaching waste liquid and stirred to dissolve to obtain a salt solution S2. S2 was added dropwise to S1 under room temperature stirring, and 1 mol / L NaOH solution was added dropwise to control the pH of the mixed solution to be 9.5-10.5. After the secondary acid leaching waste liquid was added dropwise, the mixed solution was hydrothermally crystallized at 110°C for 12 h, cooled naturally, and centrifuged for solid-liquid separation. The solid was washed with water and dried at 80°C overnight to obtain a γ-Fe2O3@ clay-loaded hydrotalcite-like dephosphorizing agent (labeled as Zr 2.5 LDH / γ-Fe2O3@Clay).
[0035] Zr 2.5 The removal rate of LDH / γ-Fe2O3@Clay for 10 mg / L phosphate was 90.46%.
[0036] Example 3
[0037] 1.0 g of the preferred γ-Fe2O3@clay was added to 20 mL of 0.0001 mol / L NaOH solution and stirred at room temperature for 30 min to obtain a turbid solution S1. 0.022 g of ZrOCl2 was added to 10 mL of the secondary acid leaching waste liquid and stirred to dissolve to obtain a salt solution S2. S2 was added dropwise to S1 under stirring at room temperature, and 1 mol / L NaOH solution was added dropwise to control the pH of the mixed solution to 9.5-10.5. After the secondary acid leaching waste liquid was added dropwise, the mixed solution was hydrothermally crystallized at 110°C for 12 h. After natural cooling, the solid-liquid separation was performed by centrifugation. The solid was washed with water and dried at 80°C overnight to obtain a γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorus agent (labeled as Zr5LDH / γ-Fe2O3@Clay).
[0038] The removal rate of Zr5LDH / γ-Fe2O3@Clay for 10 mg / L phosphate is 95.71%.
[0039] Example 4
[0040] 1.0 g of the preferred γ-Fe2O3@ clay was added to 20 mL of 0.0001 mol / L NaOH solution and stirred at room temperature for 30 min to obtain a turbid solution S1. 0.044 g of ZrOCl2 was added to 10 mL of the secondary acid leaching waste liquid and stirred to dissolve to obtain a salt solution S2. S2 was added dropwise to S1 under room temperature stirring, and 1 mol / L NaOH solution was added dropwise to control the pH of the mixed solution to be 9.5-10.5. After the secondary acid leaching waste liquid was added dropwise, the mixed solution was hydrothermally crystallized at 110°C for 12 h, cooled naturally, and centrifuged for solid-liquid separation. The solid was washed with water and dried at 80°C overnight to obtain a γ-Fe2O3@ clay-loaded hydrotalcite-like dephosphorizing agent (labeled as Zr 10 LDH / γ-Fe2O3@Clay).
[0041] Zr 10 The removal rate of LDH / γ-Fe2O3@Clay for 10 mg / L phosphate is 94.40%.
[0042] Example 5
[0043] 1.0 g of the preferred γ-Fe2O3@ clay was added to 20 mL of 0.0001 mol / L NaOH solution and stirred at room temperature for 30 min to obtain a turbid solution S1. 0.088 g of ZrOCl2 was added to 10 mL of the secondary acid leaching waste liquid and stirred to dissolve to obtain a salt solution S2. S2 was added dropwise to S1 under room temperature stirring, and 1 mol / L NaOH solution was added dropwise to control the pH of the mixed solution to be 9.5-10.5. After the secondary acid leaching waste liquid was added dropwise, the mixed solution was hydrothermally crystallized at 110°C for 12 h, cooled naturally, and centrifuged for solid-liquid separation. The solid was washed with water and dried at 80°C overnight to obtain a γ-Fe2O3@ clay-loaded hydrotalcite-like dephosphorizing agent (labeled as Zr 20 LDH / γ-Fe2O3@Clay). Zr 20 The removal rate of LDH / γ-Fe2O3@Clay for 10 mg / L phosphate is 91.63%.
Claims
1. A method for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent using natural iron-containing clay, characterized in that: The following steps are involved: Step 1: After washing, filtering, drying and grinding, the natural iron-containing clay is mixed with 100 mL of a 3 mol / L hydrochloric acid aqueous solution, stirred and refluxed at 80° C. for 4 h, and solid-liquid separation is performed after cooling to obtain acid leaching waste liquid and activated clay, the latter of which is washed with water and dried for later use; Step 2: Add 2 mol / L NaOH solution to the acid leaching waste liquid obtained in step 1 until the pH is 5.2, centrifuge to obtain secondary acid leaching waste liquid and iron hydroxide wet precipitate, mix the latter with glacial acetic acid and stir for 1 hour, hydrothermally crystallize at 100°C, filter after natural cooling, dry at 80°C for 24 hours, and calcine at 400°C under Ar atmosphere for 2 hours to obtain magnetic γ-Fe2O3; Step 3: The activated clay obtained in step 1 and the γ-Fe2O3 obtained in step 2 are dispersed in an ethanol aqueous solution with an ethanol / water volume ratio of 4:1 according to a certain mass ratio, stirred evenly, separated into solid and liquid, and the solid was vacuum dried at 60° C. for 12 h to obtain a magnetic γ-Fe2O3@clay carrier; Step 4: Add 1.0 g of the γ-Fe2O3@ clay obtained in step 3 to 20 mL of 0.0001 mol / L NaOH solution and stir at room temperature to obtain a turbid solution S1. Add ZrOCl2 to the secondary acid leaching waste liquid obtained in step 2 to obtain a salt solution S2. Under room temperature stirring, 5 to 20 mL of S2 is added dropwise to S1. At the same time, 1 mol / L NaOH solution is added dropwise to control the pH of the mixed solution to 9.5 to 10.
5. After the addition of S2 is completed, the mixed solution is hydrothermally crystallized at 110°C for 12 hours. After natural cooling, the solid-liquid separation is performed by centrifugation. The solid is washed with water and dried at 80°C overnight to obtain a γ-Fe2O3@ clay-loaded hydrotalcite-like dephosphorizer.
2. The method for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent using natural iron-containing clay according to claim 1, characterized in that: In step 1, the natural iron-containing clay is Inner Mongolia Hangjin attapulgite clay.
3. The method for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent using natural iron-containing clay according to claim 1 or 2, characterized in that: In step 2, the molar ratio of the wet precipitate of iron hydroxide to glacial acetic acid is 1:6-12, and the hydrothermal crystallization time is 12-48 hours.
4. The method for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent using natural iron-containing clay according to claim 3, characterized in that: In step 2, the molar ratio of the wet precipitate of iron hydroxide to glacial acetic acid is 1:6, and hydrothermal crystallization is performed for 24 hours.
5. The method for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent using natural iron-containing clay according to claim 1, 2 or 4, characterized in that: In step 3, the mass ratio of activated clay to γ-Fe2O3 is 10 to 30:1, and the stirring time is 4 to 10 hours.
6. The method for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent using natural iron-containing clay according to claim 5, characterized in that: In step 3, the mass ratio of the activated clay to γ-Fe2O3 is 20:1, and the stirring time is 6 hours.
7. The method for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent using natural iron-containing clay according to claim 1 or 6, characterized in that: In step 4, the amount of ZrOCl2 added to the secondary acid leaching waste liquid is 0.011 to 0.088 g.
8. The method for preparing γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorization agent using natural iron-containing clay according to claim 1 or 7, characterized in that: In step 4, the amount of ZrOCl2 added to the secondary acid leaching waste liquid is preferably 0.022 g, and S2 is preferably 10 mL.
9. Use of the γ-Fe2O3@clay-loaded hydrotalcite-like dephosphorizing agent prepared according to the method of claim 1, 2, 4, 6 or 8 in the adsorption of low-concentration phosphate in water.
Citation Information
Patent Citations
Method for preparing magnetic mesoporous composite adsorbent from natural mixed clay
CN112316894A